Single molecule tracking and analysis framework including theory-predicted parameter settings - Kuhn, Timo; Hettich, Johannes; Davtyan, Rubina; Gebhardt, J. Christof M. (Dryad, 2020)
Imaging, tracking and analyzing individual biomolecules in living systems
is a powerful technology to obtain quantitative kinetic and spatial
information such as reaction rates, diffusion coefficients and
localization maps. Common tracking tools often operate on single movies
and require additional manual steps to analyze whole data sets or to
compare different experimental conditions. We report a fast and
comprehensive single molecule tracking and analysis framework (TrackIt) to
simultaneously process several multi‐movie data sets. A user‐friendly GUI
offers convenient tracking visualization, multiple state‐of‐the‐art
analysis procedures, display of results, and data im‐ and export at
different levels to utilize external software tools. We applied our
framework to quantify dissociation rates of a transcription factor in the
nucleus and found that tracking errors, similar to fluorophore
photobleaching, have to be considered for reliable analysis. Accordingly,
we developed an algorithm, which accounts for both tracking losses and
suggests optimized tracking parameters when evaluating reaction rates. Our
versatile and extensible framework facilitates quantitative analysis of
single molecule experiments at different experimental conditions.